175k views
2 votes
A(n) = −5 ∙ 3^(x − 1)

User Frost
by
5.4k points

2 Answers

0 votes

First term:

A(n) = −5 ∙ 3^(x − 1)

A(1) = -5 * 3^(1 - 1)

A(1) = -5 * 3^0

A(1) = -5 * 1

A(1) = -5

Fourth term:

A(n) = −5 ∙ 3^(x − 1)

A(4) = -5 * 3^(4 - 1)

A(4) = -5 * 3^3

A(4) = -5 * 27

A(4) = -135

Eighth Term:

A(n) = −5 ∙ 3^(x − 1)

A(8) = -5 * 3^(8 - 1)

A(8) = -5 * 3^7

A(8) = -5 * 2187

A(8) = -10935

Best of Luck!

User Josh Ghiloni
by
5.2k points
7 votes

Answer:

A(1) = -5

A(4) = -135

A(8) = -10935

Explanation:

A(n) = -5 *3^(n − 1)

We want the first term

A(1) = -5 *3^(1 − 1)

= -5* 3^0

= -5 (1)

= -5

We want the fourth term

A(4) = -5 *3^(4 − 1)

= -5* 3^3

= -5 (27)

= -135

We want the eight term

A(8) = -5 *3^(8 − 1)

= -5* 3^7

= -5 (2187)

= -10935

User Dorian Gray
by
6.1k points